Scottish health network: promoting the health and well-being of children and young people in and leaving care - Steven McCluskey; Elaine Greaves; Carole Kean (Scottish Journal of Residential Child Care)
The health interests of young people in and leaving local authority care have received increased attention at a political and practice level in Scotland in recent years. A growing body of Scottish research is contributing to our understanding of the health needs and issues of this vulnerable and excluded group of children and young people. At the end of 2003, NHS Health Scotland led a conference that focused on the health of looked after children. This provided a much needed opportunity to bring together key stakeholders from agencies concerned with improving the health of young people in and leaving care. This event was considered to be a welcome and valuable contribution to the growing interest in this extremely important topic.